Temporal pattern of cardiovascular risk factors depending on outpatient care status - E. V. Bolotova; A. V. Kontsevaya; I. V. Kovrigina (Фундаментальная и клиническая медицина)
Aim. To study the temporal pattern of cardiovascular risk factors and cardiovascular disease (CVD) in the adult cohort depending on outpatient care status.Materials and Methods. We analyzed the incidence of CVD in the adult cohort (n = 1170) admitted to Research Institute – Ochapovsky Regional Clinical Hospital # 1 in 2015 (baseline) and after 3 years of follow-up. Groups were stratified according to the outpatient care status.Results. After 3 years of follow-up, the proportion of patients adhered to unhealthy diet decreased by 32.2%, 28.8% and 28.0% in groups without regular outpatient care, with regular outpatient care, and with regular outpatient care and CVD, respectively, as compared to baseline. Similar trend was observed regarding low physical activity (reduction by 50.3%, 24.7% and 21.8%, respectively) and tobacco smoking (45.6%, 63.0% and 61.8%, respectively). However, patients without regular outpatient care demonstrated an increase in overweight and obesity by 19.2%. Notably, the frequency of arterial hypertension increased by 48.33% in patients without regular outpatient care but decreased by 24% in those with regular outpatient care and CVD.Conclusion. During 3-year outpatient observation, we found a trend to a reduction in prevalence of cardiovascular risk factors, also in patients with CVD. Nevertheless, patients without regular outpatient care showed a statistically significant increase in prevalence of overweight, obesity and arterial hypertension.